Molecular characterization of immortalized normal and dysplastic oral cell lines. (28th August 2014) - Dickman, Christopher T. D.; Towle, Rebecca; Saini, Rajan; Garnis, Cathie
Abstract : Background: Cell lines have been developed for modeling cancer and cancer progression. The molecular background of these cell lines is often unknown to those using them to model disease behaviors. As molecular alterations are the ultimate drivers of cell phenotypes, having an understanding of the molecular make‐up of these systems is critical for understanding the disease biology modeled. Methods: Six immortalized normal, one immortalized dysplasia, one self‐immortalized dysplasia, and two primary normal cell lines derived from oral tissues were analyzed for DNA copy number changes and changes in both mRNA and miRNA expression using SMRT‐v.2 genome‐wide tiling comparative genomic hybridization arrays, Agilent Whole Genome 4x44k expression arrays, and Exiqon V2.M‐RT‐PCR microRNA Human panels. Results: DNA copy number alterations were detected in both normal and dysplastic immortalized cell lines—as well as in the single non‐immortalized dysplastic cell line. These lines were found to have changes in expression of genes related to cell cycle control as well as alterations in miRNAs that are deregulated in clinical oral squamous cell carcinoma tissues. Immortal lines—whether normal or dysplastic—had increased disruption in expression relative to primary lines. All data are available as a public resource. Conclusions: Molecular profiling experiments have identified DNA, mRNA, and miRNA alterations for a panel of normal and dysplastic oral tissue cell lines. These data are a valuable resource to those modeling diseases of the oral mucosa, and give insight into the selection of model cell lines and the interpretation of data from those lines.